2022
DOI: 10.3390/sports10080122
|View full text |Cite
|
Sign up to set email alerts
|

Serial vs. Integrated Outdoor Combined Training Programs for Health Promotion in Middle-Aged Males

Abstract: The purpose of this study was to examine and compare the training and detraining effects of outdoor serial and integrated combined exercise programs on health, functional capacity, and physical fitness indices. Fifty-one untrained overweight/obese males (47 ± 4 y) were divided into a serial combined (SCG), an integrated combined (ICG), or a control (CG) group. The SCG and ICG implemented a 3-month training (3 sessions/week) consisting of walking and body weight exercises. The only difference between SCG and IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“…The results of previous studies that implemented different combined exercise programs without chairs demonstrate conflicting results. Some of them following the results of the present study reported significant improvements in neuromuscular indices of middle-aged men and women, while others failed to observe significant neuromuscular training adaptations [ 23 , 24 , 27 , 49 , 50 , 56 ]. According to several previous investigators, the confusing results among studies concerning neuromuscular adaptations may be attributed to differences in subjects’ characteristics, loading parameters, and exercise modalities, but mainly to the order of exercises, which may reinforce the so-called “interference effect”, diminishing the efficacy of combined strength and aerobic training compared to separately training only strength or endurance [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results of previous studies that implemented different combined exercise programs without chairs demonstrate conflicting results. Some of them following the results of the present study reported significant improvements in neuromuscular indices of middle-aged men and women, while others failed to observe significant neuromuscular training adaptations [ 23 , 24 , 27 , 49 , 50 , 56 ]. According to several previous investigators, the confusing results among studies concerning neuromuscular adaptations may be attributed to differences in subjects’ characteristics, loading parameters, and exercise modalities, but mainly to the order of exercises, which may reinforce the so-called “interference effect”, diminishing the efficacy of combined strength and aerobic training compared to separately training only strength or endurance [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 73%
“…For this reason, all health and exercise organizations such as the ACSM, the WHO, and the CDC recommend the systematic participation of middle-aged and older individuals in combined exercise programs consisting of cardiovascular and neuromuscular activities as the most effective “non-pharmacological” intervention for counteracting the harmful effects of a sedentary lifestyle and aging [ 4 , 5 , 6 ]. In this context, during the last few decades, different sports and health professionals all over the world have focused on the design, implementation, and evaluation of different serial and integrated combined exercise programs using various activities and training means [ 13 , 14 , 23 , 24 , 26 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Although chair-based exercise programs have gained popularity as an alternative mode of exercise for improving health, functional capacity, and physical fitness, especially in older and frail individuals [ 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], only a few studies have examined the effects of chair-based exercise programs in healthy middle-aged individuals [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed significant improvement in aerobic capacity following basketball or street basketball (streetball) training in adults with Down syndrome [ 25 ], in adolescents with intellectual disabilities [ 52 , 53 ] and in healthy adults [ 28 , 45 ]. Furthermore, the results of the present study are comparable with other studies, which used different recreational team sport interventions (soccer/football, handball, netball) [ 13 , 14 , 16 , 17 , 22 , 33 ] as well different other exercise activities/programs (i.e., combined exercise programs, Zumba, resistance–functional training) [ 13 , 14 , 67 , 68 , 69 , 70 , 71 ] and found significant improvements in various physical fitness parameters of healthy middle-aged and older individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The reduction in blood pressure (to more normal values) following a systematic exercise intervention may eliminate the risk of cardiovascular diseases (i.e., coronary heart disease, cerebrovascular disease, rheumatic heart disease, and other conditions), which are the leading cause of death globally (taking approximately 17.9 million deaths each year) [63]. Several previous studies have shown that different recreational team-sport activities (i.e., football, floorball) [29,64,65] and other combined exercise programs using various modes of exercise [66][67][68][69][70][71] effectively decrease blood pressure (systolic and diastolic) in middle-aged individuals, supporting the results of the present study. Regarding the effect of recreational basketball training on blood pressure, there is limited information in the scientific literature with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity is a risk factor for cardiovascular and other chronic diseases, including obesity, diabetes, hypertension, and cancer [ 1 ]. Recent health promotion guidelines for children recommend accumulating a minimum of 60 min of physical activity daily as part of transportation, physical education, sport, free play, and planned exercise [ 2 ].…”
Section: Introductionmentioning
confidence: 99%